Psychoeducation: Recognising Child Maltreatment, Preventing Bullying and Strengthening Adolescents’ Self-Regulation at PPA GMIT Maranatha - Fitriananda, Triya Auliacahya; Sariano, Claudia Madyatric; Rezkita, Reifani; Ndaumanu, Joana Jafelyn; Litik, Yesica Yucita; Mouwlaka, Betshy; Aquino, Fidelis; Minggu, Remigius Febrianus; Benu, Juliana Marlin Yusrianty (Fakultas Psikologi Universitas Pancasila, 2025)
.